Institutional and Social Issues Surrounding Genetic Counselors in Japan: Current Challenges and Implications for the Global Community - Aizawa, Yayoi; Watanabe, Atsushi; Kato, Kazuto (Frontiers in Genetics, 2021)
In recent years, genetic counseling has started playing a major role in the field of genomic medicine. There are currently about 7,000 genetic counselors in more than 28 countries, with 267 certified genetic counselors in Japan alone (about 2 per million population, as of April 2020). While the rapid advancement of genomic medicine has expanded this field, the challenges genetic counselors face are also evolving. This article aims to provide an overview of the institutional and social issues surrounding genetic counselors in Japan and discuss implications for the global community. In Japan, with the rapid changes in genomic medicine and the establishment of a delivery mechanism within the healthcare system, several issues need to be discussed. First, many genetic testing, counseling, and preventive healthcare programs are not covered by public health insurance. Second, reducing human resource shortages for genetic counseling is an urgent issue. Third, the lack of a national qualification in the profession is critically important issue in the field. Fourth, research on the role and value of genetic counselors is still limited. To address these issues, discussions among relevant stakeholders, including genetic counselors, professionals in genomic medicine, and lawmakers, are necessary. Additionally, we believe that research by genetic counselors to evaluate and improve their practice and examine institutional and social issues is crucial for developing their profession’s activities and delivering high-quality healthcare to many people. To establish the position and role of the relatively new profession of genetic counselor, sharing information and collaborating on institutional and social challenges faced by genetic counselors globally will be beneficial.